Nutritional Compositions, Polyphenolic Profiles, Modulation of Gut Microbiota, Glycemic Index and Some Biological Properties of Pigmented Rice Varieties and Adlay Influenced by Soaking and Germination Conditions - Owolabi, Iyiola Oluwakemi (Prince of Songkla University, 2021)
Thesis (Ph.D., Functional Food and Nutrition)--Prince of Songkla University, 2019